Healing by Design: Physical Environment Attributes of Pediatric Healthcare Settings for Positive Health Outcomes - Babbu, Abdul Halim (New Visions in Medicine and Medical Science Vol. 8, 2024)
The parameters of the pediatric healthcare environment include the development of child-friendly environments, nature and outside views, positive distraction, therapeutic play, and family support, as a constructive diversion. The relationships among the physical environment; the individuals engaged, the tasks accomplished, the organizational protocols and, the technology utilized in the delivery of care are complex and dynamic. The term "child-friendly environment" refers to functional areas, amenities, and procedures designed to cater to the special requirements of children to promote their development, safety, and well-being. The deliberate use of play-based activities to support emotional expression, psychological coping, and physical rehabilitation among pediatric patients is referred to as "therapeutic play" in healthcare settings for children. Healthcare practitioners can develop environments that support children's healing, comfort, and resilience when they face illness or injury by using evidence-based design principles and realizing the role of the physical environment in healing.